Kajian Teoritis Organisasi dan Pengembangan Kurikulum - Sania; A. V. Prananingrum; R.E. Hidayati; F. Rossydah (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2021)
English: Curriculum is an important focus for educational institutions of various levels. Because it describes the vision, mission, and purpose of the nation's education, therefore there needs to be a good pattern and form of curriculum. A good curriculum is dynamic, can always change with the times, science and technology, culture, value system, community needs and the level of intelligence of students. Therefore, it is important that there needs to be theoretical studies related to the organization and curriculum development in order to provide more understanding. This research aims to theoretically study the organization and development of the curriculum. This type of research is qualitative research using library research method that takes data source from relevant theories. Our data analysis techniques use data reduction, data presentation, and conclusion drawing The results of this study discuss about organization and curriculum development, definition of data presentation of data, as well as the withdrawal of conclusions The results of this study discuss about the organization and development of the curriculum, the definition of curriculum development, the principles of curriculum development, models of curriculum development, definitions of curriculum organizations, and the advantages of curriculum organization Bahasa: Kurikulum merupakan sebuah tumpuan penting bagi lembaga pendidikan dari berbagai tingkat. Karena mendiskripsikan visi, misi, serta tujuan dari pendidikan bangsa, untuk itu perlu adanya pola dan bentuk kurikulum yang baik. Kurikulum yang baik adalah yang bersifat dinamis, dapat selalu mengalami perubahan seiring berkembangnya zaman, IPTEK, kultur, sistem nilai, kebutuhan masyarakat serta tingkat kecerdasan siswa. Untuk itu penting perlu adanya kajian teoritis terkait dengan organisasi dan pengembangan kurikulum supaya lebih memberikan pemahaman. Penelitian ini bertujuan untuk mengkaji secara teoritis organisasi dan pengembangan kurikulum. Jenis penelitian ini berupa penelitian kualitatif dengan menggunakan metode kajian pustaka (library research) yang mengambil sumber data dari teori-teori yang relevan. Teknik analisi data kami menggunakan reduksi data, penyajian data, serta penarikan kesimpulan Hasil penelitian ini membahas seputar organisasi dan pengembangan kurikulum, definisi pengembangan kurikulum, prinsip pengembangan kurikulum, model-model pengembangan kurikulum, Definisi organisasi kurikulum, dan kelebihan kekurangan organisasi kurikulum